Impacts of Climate Change on the Livelihoods of Local People: A Case from Jethal V.D.C., Sindhupal-Chowk District (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
Abstract not availableDOI: http://dx.doi.org/10.3126/ctbijis.v2i1.10820  Crossing the Border: International Journal of Interdisciplinary Studies Vol.2(1) 2014: 147-158